Ongoing global projects on wealth and inequality - Mariana Heredia (economic sociology. perspectives and conversations, 2023)
The World Inequality Lab (WIL), Wealth and Inequality Research Focus, CALAS Laboratory of Knowledge, and World Elite Data Base Project.
Keywords: 300